2019
DOI: 10.3390/ani9090674
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility between Humans and Their Dogs: Benefits for Both

Abstract: Simple SummaryHuman-animal interaction and its benefits have been a topic of interest in recent decades, but how this interaction can benefit both species remains unclear. In the case of companion animals, the focus of many studies is on human-dog interaction. When they live together, humans and dogs share activities, and when they share an enjoyment of daily activities such as walking and interacting with others, they are considered compatible in their activity preferences. Individuals who are more compatible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
0
7
0
2
Order By: Relevance
“…In our sample, a moderate relationship between commitment and satisfaction with the dog was observed (T1: r = 0.37, T2: r = 0.42). As recently shown in [37], the beneficial effects of dog ownership are mediated by the positive effects of shared activities, such as walking or playing. Herwijnen et al [36] found no evidence that shared activities increased relationship satisfaction.…”
Section: Discussionmentioning
confidence: 83%
“…In our sample, a moderate relationship between commitment and satisfaction with the dog was observed (T1: r = 0.37, T2: r = 0.42). As recently shown in [37], the beneficial effects of dog ownership are mediated by the positive effects of shared activities, such as walking or playing. Herwijnen et al [36] found no evidence that shared activities increased relationship satisfaction.…”
Section: Discussionmentioning
confidence: 83%
“…Behavior problems have been associated with greater ownership costs 22 24 , decreased ownership satisfaction 23 , decreased human-animal attachment 25 and poorer mental wellbeing among owners 24 26 . In contrast, compatibility between owners and their pets on key behavioral characteristics, such as enjoying exercise and getting along with peers, has been associated with greater ownership satisfaction and happiness, and decreased stress 27 , 28 . Research also indicates that caring for an animal with medical needs can increase stress and anxiety and reduce owners’ quality of life 29 31 .…”
Section: Discussionmentioning
confidence: 98%
“…It was observed how coexistence with a pet can awaken different feelings, such as joy [ 80 , 88 , 89 , 90 , 91 ] and love, in their interaction with the subjects, with very high levels seen among those who live with a pet compared to those who do not. As for the feeling of protection, those living with a pet were more likely to feel protected than those who did not live with a pet.…”
Section: Discussionmentioning
confidence: 99%